EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH THE STEM APPROACH IN LEARNING THE CONCEPT OF VOLTAIC CELL (A Study in Grade 12, Public High School 2 of Takengon) - Eva Wahyuni (Chimica Didactica Acta, 2022)
This study aims to describe the STEM approach to improve student learning outcomes in Voltaic Cell learning which was carried out in the form of action research. The research subjects were 27 students in class XII MIPA SMAN 2 Takengon, Central Aceh. The research data was obtained from the competency test at the end of each cycle. Study result data were analyzed using statistical tests (data normality test, Kolmogorov Smirnov), and comparative tests. The results of the student competency test showed that the increase in learning outcomes in the first cycle was better when compared to the previous year's learning outcomes. The test results of the second cycle experienced an increase of 6% when compared to cycle 1. The normality test showed that the data was not normal, so the comparison of the two cycles was tested using nonparametric statistics using the Mann-Witney test. The test results showed that the learning outcomes of students in cycles one and two were significantly different with a significance of 0.003 (P0.05). So it can be concluded that the application of STEM-based learning has been able to improve student learning outcomes at SMAN 2 Takengon on the Voltaic Cell concept.